2017
DOI: 10.1016/j.bbadis.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet induces brain insulin resistance and cognitive impairment in mice

Abstract: High fat diet-induced obesity is associated with insulin resistance (IR) and other chronic, diet related illnesses, including dementia. Alzheimer disease is the most common form of dementia, and is characterized by the presence of amyloid plaques and neurofibrillary tangles in brain. This study was designed to determine whether diet-induced changes in peripheral insulin sensitivity could contribute to alterations in brain insulin signaling and cognitive functions. Six week old, male C57BL/6NHsd mice were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
197
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(217 citation statements)
references
References 42 publications
13
197
0
7
Order By: Relevance
“…Mice fed a high fat diet develop obesity, lower glucose and insulin tolerance, and elicit insulin resistance in the brain, versus mice fed with a normal diet. The brains of these mice also exhibit biochemical changes associated with increased Aβ deposition and NFT formation, as well as decreased synaptic plasticity [101]. Sucrose-treated mice also show mitochondrial abnormalities, oxidative imbalance and a significant increase in Aβ levels as well as increases in phosphorylated tau (pTau) levels [102].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Mice fed a high fat diet develop obesity, lower glucose and insulin tolerance, and elicit insulin resistance in the brain, versus mice fed with a normal diet. The brains of these mice also exhibit biochemical changes associated with increased Aβ deposition and NFT formation, as well as decreased synaptic plasticity [101]. Sucrose-treated mice also show mitochondrial abnormalities, oxidative imbalance and a significant increase in Aβ levels as well as increases in phosphorylated tau (pTau) levels [102].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…This situation may cause a decrease of glucose utilization in astrocytes and subsequently reduce supports to neurons. Most of the energy and nutrition required by neurons obtained from astrocytes, and it was consistent with a change in the brain of AD, chronic hyperglycemia, and high‐fat dietary, which GLUT1 is also down‐regulated. But the mechanism of down‐regulation of GLUT1 remains to be studied.…”
Section: Discussionmentioning
confidence: 54%
“…reported no changes in the density of the glucose carriers GLUT1, widely expressed in the brain and the main glucose carrier at the BBB, and GLUT3, mainly located in neuronal membranes, in brain preparations obtained from db / db mice, when compared to wild‐type mice (Vannucci et al, ). In contrast, a recent study reported lower levels of both GLUT1 and GLUT3 in whole‐brain homogenates prepared from mice exposed to a diet rich in fat and sugar for 3 months, which develop an insulin‐resistant phenotype, relative to mice fed a regular chow (Kothari et al, ). Altogether, these observations lead us to speculate that reduced glucose transport and utilization is caused by changes in metabolic regulation according to cellular needs and adaptations to a diabetic and neurodegenerative state rather than reduced glucose carrier concentrations.…”
Section: Discussionmentioning
confidence: 89%
“…and GLUT3 in whole-brain homogenates prepared from mice exposed to a diet rich in fat and sugar for 3 months, which develop an insulin-resistant phenotype, relative to mice fed a regular chow (Kothari et al, 2017). Altogether, these observations lead us to speculate that reduced glucose transport and utilization is caused by changes in metabolic regulation according to cellular needs and adaptations to a diabetic and neurodegenerative state rather than reduced glucose carrier concentrations.…”
Section: Brain Glucose Utilizationmentioning
confidence: 96%